2018
DOI: 10.1111/acfi.12356
|View full text |Cite
|
Sign up to set email alerts
|

The type of corporate announcements and its implication on trading behaviour

Abstract: I report the empirical evidence to show how firms' expected and unexpected announcements affect investors' trading behaviour. I find that trading volume decreases before expected announcements, either scheduled or unscheduled, consistent with models that predict that discretionary liquidity traders may postpone their trading until after an anticipated news release. I also find that the magnitude of pre-announcement trading reactions is negatively associated with the level of pre-disclosure information asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…In line with Zheng (2020), trading volume will increase after the announcement is published. Ariani et al (2016) announcements about effective dates contain information that can influence investor preferences.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…In line with Zheng (2020), trading volume will increase after the announcement is published. Ariani et al (2016) announcements about effective dates contain information that can influence investor preferences.…”
Section: Resultsmentioning
confidence: 72%
“…found that after rights offering announcement causes a change in preferences for investors. Changes in liquidity around news publications reflect investors' expectations of the company's future performance(Chen et al, 2020) Zheng (2020). found that trading volume decreased on unexpected and expected announcements.…”
mentioning
confidence: 99%